Mediasi Digital sebagai Upaya Perlindungan Konsumen dalam Sengketa E-Commerce: Antara Praktik dan Kekosongan Hukum di Indonesia - Subarkah, Amirah Dwi; Gravionika, Elsa (Universitas Muhammadiyah Kotabumi, 2025)
This study aims to analyze the legal recognition of digital mediation as a dispute resolution mechanism in e-commerce transactions in Indonesia. Amid the rapid growth of electronic commerce and the increasing potential for disputes between businesses and consumers, digital mediation emerges as a fast, efficient, and cost-effective alternative. This research employs a normative juridical method with a statutory and conceptual approach, analyzing secondary data such as laws and regulations, scholarly literature, and relevant court decisions. The findings indicate that while digital mediation practices have been implemented—especially by major e-commerce platforms—there is no legal framework that explicitly regulates the procedures, the validity of mediated agreements, or the legal protection for parties involved in digital mediation. This legal vacuum creates uncertainty and challenges in enforcing mediated settlements through litigation. The study concludes that there is an urgent need for regulatory reform that explicitly acknowledges and governs digital mediation, covering procedural standards, mediator ethics, and legal recognition of mediation outcomes within Indonesia’s civil law system. Keywords: digital mediation, e-commerce disputes, alternative dispute resolution, civil law, legal certainty